1) (a+b)^3=a^3+b^3+3ab(a+b) => a^3+b^3=(a+b)^3-3ab(a+b).
Тут нам больше поможет именно эта формула
(sin^3a+cos^3a)=1/27 - sin(a)•cos(a).
Возводим в квадрат
(sina+cosa)^2=1/9
sin^2a+cos^2a + 2sin(a)•cos(a)=1/9
по основному тригометрическому тождеству
sin(a)*cos(a)=(1/9 - 1)/2=-4/9
81(sin^3a+cos^3a)=81(1/27 + 4/9)=13*81/27=39
2) sqrt(3)/2 * (cos^4*75 - cos^4*15) = sqrt(3)/2 * (cos^4(90-75) - cos^4(15)) = sqrt(3)/2 * (sin^4(15) - cos^4(15)) = sqrt(3)/2 * (sin^4(pi/12) - cos^4(pi/12) = sqrt(3)/2 * (sin^2(pi/12) + cos^2(pi/12)) * (sin^2(pi/12) - cos^2(pi/12)) = 1 * (-cos(pi/6)) = sqrt(3)/2 * (-sqrt(3)/2) = -3/4
3) 4sin2a=15sin^2a+1
преобразуем
8sina*cosa=16(sin^2a+cos^2a)
(4sina-cosa)^2=0
откуда
cosa=4sina
подставляем
28sina+4sina / 4sina+12sina = 32sina / 16sina = 2